Problems Encountered in the Translation of Terms Used in Uzbek Applied Art into English and Their Solutions - Tilavov Ikhtiyor Makhmud ugli (Global Scientific Publishing, 2023)
The aim of the study was to identify specific features of the translation of art terms from Uzbek into English. The research methods were the analysis of the text of art criticism, a comparative comparative analysis of the original and the translation of this text, as well as the method of random sampling of art history terms. As a result of the study, the main difficulties that translators may face when working with art history texts and ways to improve the quality of translations in this area were identified.
Keywords: terminology; art history; translation difficulties